Behavioral pathways and psychosocial determinants of adolescent mental health: positioning nutrition health literacy as a candidate upstream target - Wang Tuo; Wang Sicong; Lyu Wei (Frontiers in Nutrition, 2026)
Adolescence is a sensitive window for both nutritional and psychological development, and mental health problems in this group are rising worldwide. Nutrition health literacy, the capacity to obtain, understand, appraise, and apply nutrition information, has been proposed as a modifiable upstream factor that may connect dietary behavior with mental health, although evidence directly linking nutrition health literacy to mental health outcomes remains scarce. This mini review therefore synthesizes recent evidence on the behavioral and psychosocial routes to adolescent mental health, and asks how far nutrition health literacy can currently be supported as an upstream target. We first examine the multidimensional nature of nutrition health literacy, its boundaries with food literacy and mental health literacy, and the difficulty of measuring it consistently in young people. We then describe three behavioral pathways: diet, physical activity, and sleep, through which nutrition health literacy may shape emotional outcomes. Unhealthy eating patterns, such as skipping breakfast and high intake of sugar-sweetened beverages, are consistently associated with greater risks of anxiety and depression in cross-sectional work, whereas prospective cohort evidence is smaller and less consistent. We next consider psychosocial determinants operating at the family, peer, school, and sociocultural levels, which together form the ecological context of adolescent behavior. We review school- and community-based prevention programs, which show small but meaningful effects that vary across subgroups and settings. Finally, we address current controversies, including debate over universal interventions, together with major research gaps in assessment standardization, longitudinal evidence, and representation of low- and middle-income countries. We argue for culturally sensitive, equity-oriented, and developmentally appropriate approaches. Strengthening nutrition health literacy is a plausible but as yet untested target for promoting adolescent mental health, and we set out the study designs needed to test it.